(untitled) - Smith, Eric M. (New York, 1996)
This book is unique in adopting a numerical approach to the thermal design of heat exchangers. the computation of mean temperature difference. With accommodation of longitudinal conduction effects, makes full optimisation of the exchanger core possible.
Keywords: Heat exchangers; Design and construction